Pengembangan Aplikasi Monitoring Informasi Proyek Berbasis Web Menggunakan Metode ICONIX Process (Studi Kasus: PT Telkom Akses Witel Semarang) - Emmanuel Bagas Agustha; Satriyo Adhy; Dinar Mutiara Kusumo Nugraheni (Department of Informatics, Universitas Diponegoro, 2024)
This research explores the importance of a project information monitoring application in supporting effective decision-making within companies, with a focus on PT Telkom Akses Witel Semarang. Currently, internal reports are manually compiled, leading to data integration imperfections, difficulties in monitoring job billing, and potential errors in decision-making. These issues were identified as key factors motivating the development of a web-based